2018
DOI: 10.1016/j.indmarman.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

How collaborative innovation networks affect new product performance: Product innovation capability, process innovation capability, and absorptive capacity

Abstract: The current literature has investigated the direct relationship between collaborative innovation networks and new product performance, but the results are inconsistent. This research aims to explore the role of product and process innovation capabilities as two distinct mechanisms through which collaborative innovation networks improve new product performance. The study also examines the contingent effects of absorptive capacity on the relationship between collaborative innovation networks and the two innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
275
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(346 citation statements)
references
References 112 publications
7
275
0
4
Order By: Relevance
“…Enterprises need to possess a certain absorptive capacity in order to internalize external knowledge into the resources needed for innovation activities. Hence, the absorptive capacity of enterprises can significantly affect their innovation performance [29,[48][49][50][51][52][53][54]. Chaudhary and Batra [55] put forward that absorptive capacity helps the firms form proper knowledge strategies to enhance innovation performance.…”
Section: Absorptive Capacity and Innovation Performancementioning
confidence: 99%
“…Enterprises need to possess a certain absorptive capacity in order to internalize external knowledge into the resources needed for innovation activities. Hence, the absorptive capacity of enterprises can significantly affect their innovation performance [29,[48][49][50][51][52][53][54]. Chaudhary and Batra [55] put forward that absorptive capacity helps the firms form proper knowledge strategies to enhance innovation performance.…”
Section: Absorptive Capacity and Innovation Performancementioning
confidence: 99%
“…Research of innovation systems also has shown that corporative innovation processes are strongly interrelated with innovation activities in other organizations and firms [12]. This research [16] suggests that the collaboration level with different partners enhances innovation capabilities when the firm's managers have strong capacity of scanning and acquiring of external knowledge. Analysis, given in [5], shows that different types of innovations were positively affected by cooperation.…”
Section: Introductionmentioning
confidence: 75%
“…regarded innovation capabilities of product and process as two mechanisms and studied how the two mechanisms affect the performance of new products through collaborative innovation networks [17]. Xie et al studied the relationship between collaborative network and knowledge transfer performance [18].…”
Section: Complexitymentioning
confidence: 99%
“…If condition (18) is met, then it could be inferred that the trivial solution of equations (15)- (17) are moment exponentially stable. at is to say, all the players will take cooperation strategy (governments provide high subsidy, enterprises and research institutions take the strategy of substantial innovation) in the long term even though suffering from disturbance.…”
Section: Existence and Stability Of Trivial Solution For Equations (5)-mentioning
confidence: 99%